Effect of different freezing rates on Canine Spermatozoa - Geetha R (Department of Animal Reproduction, College of Veterinary and Animal Sciences, 2000)
The objective of the study was to find out the effect of different freezing rates on post thaw motility, livability and acrosomal damage of dog spermatozoa. A total of 36 ejaculates of good quality collected from SIX Dachshund dogs by digital manipulation were processed for freezing in Tris citric acid fructose egg yolk diluent containing four per cent glycerol. The processed semen samples were subjected to three different freezing protocols such as 4cm height above the liquid nitrogen level for 10 minutes (Fast freezing), Scm for 15 minutes (Moderate freezing) and 12cm for 20 minutes (Slow freezing). The mean volume of sperm rich fractions was 0.6S±0.03ml. The colour and consistency of sperm rich fractions were thin milky. The mean density of sperm rich fraction was DD(D) and mean pH was 6.63±O.02. The mean concentration of sperm rich fraction was 221±7.36 millions per ml and the average initial motility was found to be 75±O.93 per cent. The mean percentage of live sperm count, sperm abnormalities and acrosomal damage of spermatozoa was Sl.17±O.73, 5.23±O.29 and 2.32±O.25